Greek New Testament manuscripts from Albania - Lafleur, Didier. (New Testament Tools, Studies and Documents, 2018)
In Greek New Testament Manuscripts from Albania Didier Lafleur and Luc Brogly explore the riches of a unique collection of twenty-one Byzantine artefacts, among which the world-famous Beratinus 1 and Beratinus 2, both included by UNESCO in the Memory of the World Register. First described at the end of the 19th century by Anthimos Alexoudis, then revealed to Western scholarship by Pierre Batiffol, yet this collection has remained unknown to textual critics and no major analysis of it has been performed in over a century. Based on a fresh autopsy of the documents, the book describes the artefacts physically and analyses textual features and variant readings of each. This monograph will be of vital interest to any scholar or advanced student in the fields of Greek New Testament textual criticism and codicology.